Evaluation of Nectin-4 and Trop-2: Implications for Patient Outcomes and Therapy in Penile Cancer - Mink, Jan Niklas; Eckstein, Markus; Khalmurzaev, Oybek; Pryalukhin, Alexey; Geppert, Carol-Immanuel; Lohse, Stefan; Bende, Kristóf; Lobo, João; Henrique, Rui; Loertzer, Hagen; Steffens, Joachim; Jerónimo, Carmen; et al. (Modern Pathology, 2025)
Metastatic penile cancer (PC) continues to have a poor prognosis because of inadequate treatment options. Enfortumab vedotin and sacituzumab govitecan are antibody-drug conjugates (ADCs) that have significantly improved the prognosis of several other tumor types and are, therefore, promising candidates for the successful treatment of metastatic PC. We examined the expression of ADC targets Nectin-4 and Trop-2 in an international multicenter cohort of 203 PC patients both in the primary tumor and in metastases. In addition, we evaluated their prognostic values. Either intermediate or high Nectin-4 membrane expression was found in 28.0% of primary tumors and 18.8% of metastases. The expression in primary tumor decreased significantly with increasing T stage (P ≤ .001). It did not correlate with human papillomavirus status (P = .307) and was not associated with metastasis-free survival, cancer-specific survival, or overall survival. Nectin-4 expression levels at the tumor front and in metastases were significantly associated with each other (P = .005). Trop-2 was detected on the membrane of almost all samples with intermediate or high expression (primary tumor, 98.1%; metastasis, 100%). It was not associated with metastasis-free survival, cancer-specific survival, or overall survival. The expression at tumor front was significantly increased in human papillomavirus–positive tumors (P = .005). Neither Nectin-4 nor Trop-2 was found to be of prognostic value in PC. Enfortumab vedotin therapy seems promising for selected patients with high Nectin-4 expression, which should be confirmed in PC metastases before treatment is considered. Trop-2 is highly expressed in almost all PCs, and therefore, it is a very interesting potential target for sacituzumab govitecan therapy. Both ADCs warrant investigation in clinical trials focusing on PC.
CRIS-Team Scopus Importer:2025-05-23
Keywords: antibody-drug conjugate; immunohistochemistry; Nectin-4; penile squamous cell carcinoma; Trop-2